2012
DOI: 10.1096/fj.11-202333
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune agonist, dsRNA, induces apoptosis in ovarian cancer cells and enhances the potency of cytotoxic chemotherapeutics

Abstract: Ovarian cancer is the most lethal gynecological cancer. Here we show that innate immune agonist, dsRNA, directly induces ovarian cancer cell death and identify biomarkers associated with responsiveness to this targeted treatment. Nuclear staining and MTT assays following dsRNA stimulation revealed two subpopulations, sensitive (OVCAR-3, CAOV-3; patient samples malignant 1 and 2) and resistant (DOV-13, SKOV-3). Microarray analysis identified 75 genes with differential expression that further delineated these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…IFN-␤ is known to be a key molecule in antitumoral immune response in various cancers, including PCa (40,41). Moreover, in different cancer models, IFN-␤ has been shown to mediate poly(I:C)-dependent apoptosis or growth arrest (2,37,38). In contrast, in this work, by using neutralizing antibody against IFNR, we demonstrate that in-poly(I:C)-induced apoptosis takes place independently of IFN-␤ in androgen-independent PCa cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-␤ is known to be a key molecule in antitumoral immune response in various cancers, including PCa (40,41). Moreover, in different cancer models, IFN-␤ has been shown to mediate poly(I:C)-dependent apoptosis or growth arrest (2,37,38). In contrast, in this work, by using neutralizing antibody against IFNR, we demonstrate that in-poly(I:C)-induced apoptosis takes place independently of IFN-␤ in androgen-independent PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…After demonstrating that in-poly(I:C)-apoptosis is IRF3-independent but is accompanied by IFN-␤ increased expression, we evaluated whether IFN-␤ mediates in an autocrine fashion in-poly(I:C)-triggered apoptosis, as described previously in different cancer cell lines (2,37,38). With this aim, we blocked type I interferon receptor (IFNR-1) by a neutralizing antibody, and we assessed apoptosis rate after in-poly(I:C) treatment in PC3 cells.…”
Section: Tlr3 and Src Mediate Apoptosis Independently Of Irf3mentioning
confidence: 99%
“…Moreover, I expect heteroclitic/heterospecific actions by poly(ADP-ribose) sensitization in vivo , as seen, for example, in a report by Sibley et al 97) In this context, the possible presence with as yet undetermined naturally occurring double stranded RNAs may augment its function in which innate immunity and Toll-like receptors (TLRs) are involved. 98102) In this sense, it might be of use to apply the classic method to produce a large amounts of poly(ADP-ribose) as far as calf thymuses a source of PARP are available. 103) …”
Section: Discussionmentioning
confidence: 99%
“…We first determined potency of these short ssRNA in eliciting antiviral responses in a human ovarian epithelial carcinoma cell line (SKOV3 cells), which have been previously used as a model to study the immunogenicity of different types of RNA [38][39][40]. Using IFNb expression as a benchmark for antiviral responses, our data showed that only 3p-ssRNA with longer than 60 nt induced IFNb, whereas the removal of the 3p group completely abolished this effect, as demonstrated in the case of 3p-80nt-ssRNA (Fig.…”
Section: Wang Et Almentioning
confidence: 99%